2012
DOI: 10.1016/j.joca.2012.06.017
|View full text |Cite
|
Sign up to set email alerts
|

Comparative effectiveness of alternative clinical pathways for primary hip and knee joint replacement patients: a pragmatic randomized, controlled trial

Abstract: While effect sizes were small compared with major effects of the surgery itself, an evidence-informed clinical pathway can improve health related quality of life (HRQoL) of hip and knee arthroplasty patients with degenerative joint disorder in routine clinical practice for up to 12 months post-operatively. CLINICALTRIALS.GOV IDENTIFIER: NCT00277186.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
51
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(55 citation statements)
references
References 27 publications
3
51
0
1
Order By: Relevance
“…. Thirty‐eight eligible studies with relevant outcomes were found, including two quasi‐randomized studies. In total 67 papers on these studies were reviewed ( Appendix S1 , supporting information).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…. Thirty‐eight eligible studies with relevant outcomes were found, including two quasi‐randomized studies. In total 67 papers on these studies were reviewed ( Appendix S1 , supporting information).…”
Section: Resultsmentioning
confidence: 99%
“…Twenty studies reporting length of stay had standardized discharge criteria. In one the criteria differed between intervention and control groups. In another study length of stay was explicitly part of the intervention, with discharge planned for day 3 in the intervention group and day 6 for the control group.…”
Section: Resultsmentioning
confidence: 99%
“…An indication of limited capacity in rural regions that was seen in this survey was a trend toward fewer therapy sessions reported by rural physiotherapists relative to the physiotherapists in urban settings. The pressure on providing physiotherapy in the community was also felt with the decreasing LOS for TJA, which has shifted the provision of rehabilitation services from the acute care setting into the community where little standardization in care exists [23, 34]. While the focus of the acute care pathway is to prepare patients for discharge, little focus has been directed toward the delivery of services in the community once the patient has been discharged.…”
Section: Discussionmentioning
confidence: 99%
“…While the focus of the acute care pathway is to prepare patients for discharge, little focus has been directed toward the delivery of services in the community once the patient has been discharged. No clinical pathway or quality indicators exist in the community for rehabilitation services [23]. Future work is required to determine how post discharge services should be organized and identify approaches to optimize patient outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation